2019
DOI: 10.3390/ijms20051147
|View full text |Cite
|
Sign up to set email alerts
|

Fomes fomentarius Ethanol Extract Exerts Inhibition of Cell Growth and Motility Induction of Apoptosis via Targeting AKT in Human Breast Cancer MDA-MB-231 Cells

Abstract: Fomes fomentarius, an edible mushroom, is known to have anti-cancer, anti-inflammatory, and anti-diabetes effects. However, the underlying anti-cancer mechanism of F. fomentarius is unknown. To determine the molecular mechanism of the anti-cancer effects of F. fomentarius, various methods were used including fluorescence-activated cell sorting, Western blotting, migration, and crystal violet assays. F. fomentarius ethanol extract (FFE) decreased cell viability in six cancer cell lines (MDA-MB-231, MCF-7, A549,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…β-Thujaplicin is a natural monoterpenoid that can induce G0/G1 phase cell-cycle arrest, as well as regulate cell-cycle mediators, cyclin D1, cyclin E, and CDK4, thereby inhibiting the proliferation of ER-basal-like MCF10DCIS.com human BC cells [156]. The Fomes fomentarius ethanol extract (FFE) arrests the S and G2/M cell populations by inhibiting the expression of cell-cycle regulatory proteins, such as CDK2, cyclin A/E, and S-phase kinase-associated protein 2 (Skp2), leading to apoptosis via targeting AKT and a reduction in the migration of MDA-MB-231 cells [157]. Recently, researchers found that a new water soluble bis(hydroxymethyl) alkanoate curcuminoid derivative, MTH-3, participates in G2/M phase arrest in MDA-MB-231 cells by downregulating the expression of CDK1 [158].…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…β-Thujaplicin is a natural monoterpenoid that can induce G0/G1 phase cell-cycle arrest, as well as regulate cell-cycle mediators, cyclin D1, cyclin E, and CDK4, thereby inhibiting the proliferation of ER-basal-like MCF10DCIS.com human BC cells [156]. The Fomes fomentarius ethanol extract (FFE) arrests the S and G2/M cell populations by inhibiting the expression of cell-cycle regulatory proteins, such as CDK2, cyclin A/E, and S-phase kinase-associated protein 2 (Skp2), leading to apoptosis via targeting AKT and a reduction in the migration of MDA-MB-231 cells [157]. Recently, researchers found that a new water soluble bis(hydroxymethyl) alkanoate curcuminoid derivative, MTH-3, participates in G2/M phase arrest in MDA-MB-231 cells by downregulating the expression of CDK1 [158].…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…Fomes fomentarius has diverse medicinal applications including anti-bacterial, anti-diabetes, anti-inflammatory and antioxidant activities [ 39 , 40 ]. As dry milling produces a fine powder which can be stored for months and also easily transported, practical applications of these materials are not farfetched, for instance as wound dressings, antioxidant food supplements, agricultural fertilizers and plant protectants, cosmetics, sunscreens, and possibly even as materials, for instance as redox filters in the treatment of oxidizing waste ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Betulin in the extract inhibited p-AKT in MDA-MB-231 cells. Thus, the phosphoinositide 3kinase/AKT pathway was suppressed (Lee et al, 2019b).…”
Section: Fomes Fomentariusmentioning
confidence: 99%